Comparison of Short-Term Memory Levels of Stunted and Non-Stunted Children Aged 2–5 Years (Majalah Kedokteran Bandung, 2026)
Stunting remains a significant public health issue in developing countries, including Indonesia as it can adversely affect children's growth and development, particularly impairing the maturation of memory functions that may subsequently lead to diminished cognitive abilities. While the effects of stunting on memory functions have been investigated in Indonesia in the past, the findings have yielded inconsistent results. This cross-sectional study aimed to comparatively analyze the short-term memory levels in stunted versus non-stunted children aged 2–5 years in the area of Batua Community Health Center, Makassar City, Indonesia from August to October 2024. Short-term memory levels were evaluated using the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) assessment. Stunting was determined through height-for-age (H/A) indicators, utilizing a Z-score threshold of less than -2. Data were subsequently analyzed using the Chi-Square test. Among the 114 participants, most were classified as non-stunted (n=76; 66.7%), yet a significant proportion demonstrated suboptimal short-term memory levels (n=75; 65.8%). Both stunted and non-stunted groups predominantly exhibited suboptimal performance in short-term memory, with no significant difference identified between the groups (p=0.675). In conclusion, the findings suggest that stunting is not associated with impairments in short-term memory among children aged 2-5 years. Further research involving multiple centers is warranted to validate these results.
Keywords: Growth and development; memory; nutritional status; stunting